Body size and diet breadth drive local extinction risk in butterflies - Anwar Palash; Shatabdi Paul; Sabrina Karim Resha; Md Kawsar Khan (Heliyon, 2022)
Lepidoptera, butterflies and moths, are significant pollinators and ecosystem health indicators. Therefore, monitoring their diversity, distribution, and extinction risks are of critical importance. We aim to understand drivers of local extinction risks of the butterflies in Bangladesh. We conducted a systematic review to extract local extinction risks of the butterflies of Bangladesh, and possible drivers (e.g., body size and diet breadth) of their extinction. We tested whether body size, larval host plants and adult nectar plants contribute to the local extinction risks of butterflies. We predicted butterflies with larger body size and fewer host and nectar plants would be in greater extinction risk. We showed extinction risk is higher in larger butterflies than smaller butterflies, and in butterflies with fewer number of host and nectar plants than the butterflies with higher number host and nectar plants. Our study identifies body size and diet breadth as a potential driver of the local extinction of butterflies thereby suggesting larger conservation urgency for the larger butterflies with narrow diet breadth.